Effect of primary selective laser trabeculoplasty on tonographic outflow facility: a randomised clinical trial. Issue 11 (14th May 2010) - Goyal, Saurabh; Beltran-Agullo, Laura; Rashid, Safina; Shah, Shaheen P; Nath, Remin; Obi, Adanna; Lim, K Sheng
Abstract : Purpose: To investigate the effect of 180° versus 360° primary selective laser trabeculoplasty (SLT) on tonographic outflow facility and intraocular pressure (IOP). Design: Prospective, single masked randomised clinical trial. Participants: Patients with untreated primary open angle glaucoma or ocular hypertension both with IOP >21–35 mmHg. Methods: 40 patients randomly treated with 180° or 360° SLT after baseline tonographic outflow facility (electronic Schiøtz tonography) and IOP measurements were repeated after 1 month. One eye from each patient was randomly selected for analysis. Eight untreated eyes were included as a control group. Main Outcome Measures: Tonographic outflow facility and IOP difference. Responders were defined as having at least a 20% reduction in IOP. Results: Three patients were excluded due to poor tonography. There were 18 eyes in the 180° group and 19 eyes in the 360° group. Tonographic outflow facility increased significantly (180° p=0.003, 360° p=0.005) and IOP decreased significantly (180° and 360° p<0.001) from baseline. There were no significant differences between the two groups as regards the increase in tonographic outflow facility (180° group 37.5%, 360° group 41%, p=0.23) and decrease in IOP (180° group 24%, 360° group 35%, p=0.35). There were similar number of responders in 180° group (72%) as compared to 360° group (89.5%, p=0.23). Tonographic outflow facility and IOP did not change significantly from baseline in the control group (tonographic outflow facility: 8% increase p=0.48, IOP: 4% decrease p=0.33). Conclusions: Primary SLT significantly increased the tonographic outflow facility and decreased IOP in patients with primary open angle glaucoma and ocular hypertension but no statistically significant differences were found between the 360° and 180° groups. The level of IOP reduction due to primary SLT treatment could not be explained by the increase in tonographic outflow facility alone. Clinical trial registration: ISRCTN66330584, Current Controlled Trials. 1/11/2006